Pregnancy and COVID-19: past, present and future - Young Keun Kim; Eui Hyeok Kim (Obstetrics & Gynecology Science, 2023)
Current evidence suggests that severe acute respiratory syndrome coronavirus 2 infection is associated with an increased incidence of adverse severe maternal and perinatal outcomes. However, vertical transmission is rare. The management of pregnant women with coronavirus disease 2019 (COVID-19) is similar to that of non-pregnant women, and effective treatments, including antiviral therapy, dexamethasone, and prophylactic anticoagulation should not be withheld during pregnancy. During the early COVID-19 pandemic period, the management of pregnant women was often delayed until the polymerase chain reaction (PCR) results came out or due to close contact, even among those without symptoms. Out of concern for the spread of infection, cesarean sections were performed instead of vaginal birth, since infection could have led to an increase in maternal and neonatal morbidities. Additionally, if the maternal PCR test was positive, the neonate was quarantined, and despite infectivity decreasing 10 days after symptom onset. It is necessary to ease the strict measures of infection control in the field of obstetrics. The presence or absence of maternal COVID-19 symptoms should be identified to stratify the risk, and vaginal delivery can be attempted in asymptomatic women with low infectivity. With more women being vaccinated safety data about vaccination is rapidly accumulating and no concerns have been detected. Globally, COVID-19 vaccines are recommended even during pregnancy. In order to prepare for future pandemics, it is necessary to apply lessons learned from this pandemic. Policymakers and healthcare leaders must determine efficient and effective strategies for preserving safe maternal care, even during an ongoing global emergency.